2017
DOI: 10.1016/j.neuint.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

APP/Aβ structural diversity and Alzheimer's disease pathogenesis

Abstract: The amyloid cascade hypothesis of Alzheimer’s disease (AD) proposes amyloid-β (Aβ) is a chief pathological element of dementia. AD therapies have targeted monomeric and oligomeric Aβ 1-40 and 1-42 peptides. However, alternative APP proteolytic processing produces a complex roster of Aβ species. In addition, Aβ peptides are subject to extensive posttranslational modification (PTM). We propose that amplified production of some APP/Aβ species, perhaps exacerbated by differential gene expression and reduced peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 224 publications
(177 reference statements)
0
83
0
Order By: Relevance
“…With the recognition of the fact that many proteins (Aβ, TAU, prion protein Prion (PrP), Huntingtin and α-synuclein) are the substrate of the aggregation-prone PTMs Sp [6], we are focusing, primarily, on the racemization of the Aβ. The amyloid precursor protein (APP) is one of the most studied proteins concerning pathological misfolding.…”
Section: Racemization Of the Aβmentioning
confidence: 99%
“…With the recognition of the fact that many proteins (Aβ, TAU, prion protein Prion (PrP), Huntingtin and α-synuclein) are the substrate of the aggregation-prone PTMs Sp [6], we are focusing, primarily, on the racemization of the Aβ. The amyloid precursor protein (APP) is one of the most studied proteins concerning pathological misfolding.…”
Section: Racemization Of the Aβmentioning
confidence: 99%
“…However, no clear correlation could be made between plasma Aβ fragment concentrations and AD, dementia and various stages of cognitive decline, perhaps in part due to the limited sensitivity of the current analytical methods [156]. Due to observed discrepancies between AD dementia and amyloid deposition, some groups have suggested that either soluble oligomeric Aβ peptides may be more toxic, or that tau neurofibrillary tangles may be the pathogenic species [157]. …”
Section: Proteases and Diseasementioning
confidence: 99%
“…Amyloid plaques are aggregates of amyloid beta (Aβ) peptide derived mainly from the cleavage of a transmembrane protein named amyloid precursor protein (APP) by the sequential action of two aspartyl protease enzymes, β-and γ-secretases (amyloidogenic pathway) in which the APP is firstly cleaved by β-secretase to soluble APP and residual C-terminal segment that is further digested by the γ-secretase to Aβ-40/42 segments. The insoluble Aβ aggregates start to appear 15-25 years prior to the onset of cognitive decline or tau pathology, and their formation is triggered by enhancement of the amyloidogenic pathway with increasing the pool of soluble Aβ production, which in turn aggregate to form monomeric, oligomeric, protofibrils and finally mature insoluble Aβ [10]. Under normal circumstances, the ratio of Aβ-42: Aβ-40 is 1:9 and increase in this ratio due to either aberrant production (increased γ-secretase activity) or clearance (abnormal microglial activities) is the cause of Aβ accumulation as the former has a high tendency to aggregate.…”
Section: The Amyloid Hypothesismentioning
confidence: 99%
“…Many studies revealed that people with a rare missense mutation (rs75932628-T) in the gene encoding TREM2 (Triggering Receptor Expressed on Myeloid Cells 2) are at increased risk of developing AD 2-3 folds than others possibly due to reduced clearing abilities of their microglia to Aβ and apoptotic cells [10]. At the same time, other studies suggested a possible role of epigenetic changes and aberrantly expressed micro-RNAs (miRNAs) in the pathogenesis of AD through disturbing neurogenesis, synaptic plasticity, synaptogenesis and neuronal network preservation as well as enhancing Aβ production and neuroinflammation [27].…”
Section: Genetics and Epigenetics Of Admentioning
confidence: 99%